Synthesis of azobenzenophanes with a large molecular cavity - Rajakumar, Perumal; Senthilkumar, B.; Srinivasan, Kannupal (Australian Journal of Chemistry, 2006)
The design and synthesis of four large-cavity azobenzenophanes, capable of forming photochemically controllable complexes with organic guest molecules, are described. These azobenzenophanes, possessing m-terphenyl, aromatic carbonyl, and chiral BINOL spacers, were synthesized from the corresponding bisphenols and dibromides using simple O-alkylation methodology. A preliminary photochemical study was carried out on the aromatic carbonyl spacer containing azobenzenophane, and the isosbestic points for the cis–trans isomerization process appeared at 319 and 419 nm.